Assessment of cardiac hemodynamics indicators in patients with arterial hypertension and non-alcoholic fatty liver disease depending on angiotensin II type 1 receptor A1166C gene polymorphism - O. Ya. Babak; M. M. Zaitseva (Zaporožskij Medicinskij Žurnal)
Aim of study is to estimate the indicators of cardiac hemodynamics in patients with arterial hypertension and non-alcoholic fatty liver disease depending on angiotensin II type 1 receptor (A1166C) gene polymorphism.